The Phenomenon of the Brick and Click Strategy in Empowering Business Ecosystems in the Digital Age - Widnyani, Ni Made; Astitiani, Ni Luh Putu Surya; Rettobjaan, Vitalia Fina Carla; Aristayudha, A.A. Ngurah Bagus; Richadinata, Kadek Riyan Putra (Global Health Science Group, 2023)
The rapid development of the digital era has spawned various strategic methods or techniques that can be used by business actors both online and offline. Brick and Click is one of the business strategies used by companies to integrate offline and online businesses into one unit that is currently being loved by consumers and business movers. The purpose of this research is to find out more deeply about the phenomenon of implementing the Brick and Click strategy used by business activists in Empowering Business Ecosystems in the Digital Age. In this study used a qualitative research method with a phenomenological approach where researchers collected data by interviewing 4 main participants and 2 participants as triangulation who had carried out the Brick and Click strategy for approximately one year. After the data is collected, the data is sorted and analyzed and finally conclusions are drawn. The research results produced four themes in the Brick and Click method, namely the concept of the Brick and Click method, how to implement the Brick and Click method, the obstacles and advantages of the Brick and Click method, and the role of inventory management. The use of the Brick and Click strategy provides great benefits for business drivers and consumers.